Mediasi Sebagai Asas Primum Remidium Dalam Penyelesaian Sengketa Pelayanan Kesehatan Berbasis Keadilan Proporsional: Mediation As The Primum Remidium Principle In Health Service Dispute Resolution Based On Proportional Justice - Nugroho, Hari Pudjo (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
Since the enactment of Law 17/2023, it has opened a new paradigm and confirmed how the mandate for resolving disputes in the health sector is carried out, which places alternative dispute resolution as the main and first thing before other legal remedies are used by the parties to the dispute. As an a contrario logic in the application of criminal law as the ultimum remidium principle, dispute resolution outside of court for dispute cases as regulated in Article 310 of Law 17/2023 is an application of the primum remidium principle. The concept of Primum Remidium as a legal order in resolving disputes resulting from health services in Law 17/2023 and mediation being the main choice in resolving disputes resulting from health services in a just manner is an important thing. The research method used is normative legal research based on a statute approach and a conceptual approach. The result is this approach to resolving criminal allegations of doctors in providing health services through restorative justice is a primum remidium step to return the function of criminal law to its track, namely as an ultimum remidium function and as a last resort weapon when other legal remedies cannot be used as a deterrent effect for a doctor. In the settlement process by means of deliberation to reach consensus, justice is created by the parties. The discussion of fairness in resolving medical disputes through mediation is based on balance and proportion. In this case the parties will take their respective proportions, justice is created through their own agreement. Starting from this idea of justice, the parties to the dispute use their own criteria for justice.